EVALUATING ACADEMIC PERFORMANCE AND CURRICULUM RELEVANCE IN A NATURE CONSERVATION SCIENCE QUALIFICATION: A CROSS-SECTIONAL QUANTITATIVE STUDY. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2025)
Introduction Ensuring alignment between academic performance and curriculum relevance is vital in Nature Conservation education, especially in preparing graduates for the demands of the industry. This study evaluates the Animal Studies 3 module within the Bachelor of Applied Science in Nature Conservation at Mangosuthu University of Technology (MUT), focusing on performance trends and curriculum alignment with industry expectations. Methods A cross-sectional quantitative research design was used. Academic records from 150 students (2019–2023) were analyzed to assess performance trends. Additionally, a survey involving 200 participants, students, lecturers, and industry professionals was conducted to evaluate perceptions of curriculum relevance. Descriptive and inferential statistical methods were employed to analyze both academic outcomes and stakeholder feedback. Results Pass rates improved from 75% in 2019 to 82% in 2023, with a dip in 2022 attributed to curriculum changes. Despite this improvement, stakeholder feedback highlighted a gap between theoretical knowledge and fieldwork competence. Only 40% of industry professionals deemed the curriculum highly relevant, and 20% recommended updates. Students reported difficulties applying theoretical concepts in practical contexts, while lecturers noted insufficient field-based training. Conclusion Although academic performance has improved, a disconnect remains between classroom learning and real-world conservation skills. The current curriculum does not fully equip students for field application. Recommendation To enhance the relevance and impact of the Animal Studies 3 module, the curriculum should incorporate more practical, hands-on learning experiences that allow students to apply theoretical concepts in field-based settings. Regular curriculum reviews involving both academic staff and industry stakeholders are essential to ensure alignment with evolving conservation demands. Furthermore, targeted academic support should be provided to lower-performing students to improve outcomes, and strategic partnerships with conservation agencies should be strengthened to facilitate real-world exposure and graduate preparedness.